Growth physiology, genomics, and proteomics of Desulfurivibrio dismutans sp. nov., an obligately chemolithoautotrophic, sulfur disproportionating and ammonifying haloalkaliphile from soda lakes - Sorokin, Dimitry Y.; Merkel, Alexander Y.; Ziganshin, Rustam H.; Kublanov, Ilya V. (Frontiers in Microbiology, 2025)
Elemental sulfur disproportionation combined with obligate autotrophy is a unique type of sulfur-based anaerobic metabolism known in a limited number of bacteria, primarily found among the members of Desulfobacterota phylum. Until recently, the only characterized alkaliphilic representative of this group was Desulfurivibrio alkaliphilus, originally isolated as an H2-dependent sulfur reducer. In this study, we describe the properties of a novel species within this genus, Desulfurivibrio dismutans strain AMeS2, which was originally enriched and isolated from a soda lake sample as an autotrophic elemental sulfur disproportionating bacterium. Similar to D. alkaliphilus AHT 2T, D. dismutans AMeS2 is an obligately alkaliphilic and moderately salt-tolerant autotrophic bacterium. In contrast to known neutrophilic sulfur disproportionating bacteria, it is capable of disproportionating sulfur without Fe(III). It can also grow by dissimilatory sulfur reduction to sulfide or nitrate reduction to ammonium (DNRA) with formate (but not with H2) as the electron donor. The addition of formate to sulfur-disproportionating AMeS2 culture significantly increased the sulfur-reducing activity but did not completely abolish the oxidative branch of sulfur disproportionation. Genome analysis confirmed the presence of dissimilatory sulfur oxidation and dissimilatory sulfur and nitrate reduction machineries in the strain. S0 disproportionation occurs by means of cytoplasmic dissimilatory sulfite reductase (Dsr) donating electrons to, and periplasmic polysulfide reductase (PsrABC) receiving electrons from the menaquinone pool. Nitrate reduction to ammonium (DNRA) occurs by the combined action of a membrane formate dehydrogenase FdnGHI, periplasmic nitrate reductase, and octaheme c ammonifying nitrite reductase. Autotrophic growth is enabled by the Wood–Ljungdahl pathway (WLP). The genome also encodes proteins that presumably connect the oxidative branch of sulfur disproportionation with the carbon (WLP) cycle. Comparative proteomics of cells grown by sulfur disproportionation and formate-dependent DNRA demonstrated overexpression of the genes encoding Psr and rDSR at sulfur-disproportionating conditions, confirming their key role in this process. On the contrary, the genes encoding DNRA proteins are upregulated in the presence of nitrate. Thus, genomic and proteomic analyses revealed the pathways for energy conservation in a new representative of Desulfurivibrio growing at DNRA and under the thermodynamically challenging conditions of sulfur disproportionation.